Decision Support System Development Through GIS for Computer Aided River Management and Enhanced Agricultural Productivity - Saher, Faisal Nadeem; Nasly, Mohamed Ali; Tuty Asmawaty, Abdul Kadir; Nasehir Khan, Yahaya (2013)

(untitled)
Managing river is an acute and more attentive area where it faces heavy water feeds due to rains and problems of sedimentation caused by high sloped terrain in catchment.